Stent revascularization for the prevention of cardiovascular and renal events among patients with renal artery stenosis and systolic hypertension: Rationale and design of the CORAL trial - Cooper, Christopher J.; Murphy, Timothy P.; Matsumoto, Alan; Steffes, Michael; Cohen, David J.; Jaff, Michael; Kuntz, Richard; Jamerson, Kenneth; Reid, Diane; Rosenfield, Kenneth; Rundback, John; Agostino, Ralph D'; et al. (The American heart journal, 2006)
Atherosclerotic renal artery stenosis is a problem with no consensus on diagnosis or therapy. The consequences of renal ischemia are neuroendocrine activation, hypertension, and renal insufficiency that can potentially result in acceleration of atherosclerosis, further renal dysfunction, myocardial infarction, heart failure, stroke, and death. Whether revascularization improves clinical outcomes when compared with optimum medical therapy is unknown. CORAL is a randomized clinical trial contrasting optimum medical therapy alone to stenting with optimum medical therapy on a composite cardiovascular and renal end point: cardiovascular or renal death, myocardial infarction, hospitalization for congestive heart failure, stroke, doubling of serum creatinine, and need for renal replacement therapy. The secondary end points evaluate the effectiveness of revascularization in important subgroups of patients and with respect to all-cause mortality, kidney function, renal artery patency, microvascular renal function, and blood pressure control. We will also correlate stenosis severity with longitudinal renal function and determine the value of stenting from the perspectives of quality of life and cost-effectiveness. The primary entry criteria are (1) an atherosclerotic renal stenosis of ≥60% with a 20 mm Hg systolic pressure gradient or ≥80% with no gradient necessary and (2) systolic hypertension of ≥155 mm Hg on ≥2 antihypertensive medications. Randomization will occur in 1080 subjects. The study has 90% power to detect a 28% reduction in primary end point hazard rate. CORAL represents a unique opportunity to determine the incremental value of stent revascularization, in addition to optimal medical therapy, for the treatment of atherosclerotic renal artery stenosis.